PENGARUH PRAKTIK MICRO TEACHING TERHADAP KOMPETENSI PEDAGOGIK MAHASISWA PENDIDIKAN EKONOMI PADA KURIKULUM MERDEKA BELAJAR - Sigiro, Yescenia; Eki Monalisa Br Surbakti; Agnes Dea Lita Br Sitepu; Deni Adriani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the influence of micro teaching practice on the pedagogic competence of Economics Education students in the Independent Learning Curriculum. This study uses a quantitative method with data collection techniques through questionnaires given to students of Economics Education, State University of Medan. The research sample amounted to 30 students which was determined by simple random sampling technique. Data analysis was carried out using simple linear regression with the help of the SPSS 26 application. The results showed that the practice of micro teaching had a positive influence on students' pedagogic competence with a regression equation of Y = 0.957 + 0.939X. The results of the t-test showed that the t-value of the calculation of 25.921 was greater than the t-table of 2.048 with a significance value of < 0.05 so that the research hypothesis was accepted. In addition, the results of the determination coefficient test showed an R Square value of 0.959 or 95.9%, which means that students' pedagogic competence can be explained by the micro teaching variable of 95.9%, while the remaining 4.1% is influenced by other factors that were not studied in this study. Thus, it can be concluded that the practice of micro teaching has a significant influence on improving the pedagogic competence of Economics Education students. Keywords: Micro Teaching, Pedagogic Competence, Independent Curriculum